Teachers’perception on English Curriculum and Material in Vocational High School - Astuti, Sari; Kokom Nurjanah (JOLADU: Journal of Language Education, 2023)
Vocational High School (VHS)Students are expected to work directly upon completing their study. Thus, the curriculum and material should be relevant with their majors since the skills are necessary to enter the workforce, including their English skills. The implementation of curriculum and material in VHS should have different characteristic from the ones implemented in Senior High School. English curriculum and material in VHS should contain and produce the aspects of work skills. The aim of this study is to investigate the VHS English teachers’ perception on curriculum and material implemented in VHS. The research applied descriptive qualitative research design that involved three VHS teachers in Depok as respondent. Semi-structured interview was conducted to collect the data. The study shows that teachers have unfavorable perception towards the English curriculum and material implemented in VHS. The result implies that the content of English curriculum and material are similar to the ones taught in Senior High Schools and thus are not relevant to VHS students’ needs to enter the workforce. They suggest that English curriculum and material in VHS should be integrated to the students’majors and propose ESP as the type of English implemented in VHS. Having ESP in VHS will enable students to improve their Englih skills relevant to their needs of working and eventually help them to compete in the global workforce.